2003
DOI: 10.1007/s00122-003-1243-y
|View full text |Cite
|
Sign up to set email alerts
|

An apricot (Prunus armeniaca L.) F2 progeny linkage map based on SSR and AFLP markers, mapping plum pox virus resistance and self-incompatibility traits

Abstract: A genetic linkage map of apricot ( Prunus armeniaca L.) was constructed using AFLP and SSR markers. The map is based on an F(2) population (76 individuals) derived from self-pollination of an F(1) individual ('Lito') originated from a cross between 'Stark Early Orange' and 'Tyrinthos'. This family, designated as 'Lito' x 'Lito', segregated for two important agronomical traits: plum pox virus resistance (PPV) and self-incompatibility. A total of 211 markers (180 AFLPs, 29 SSRs and two agronomic traits) were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 59 publications
7
89
3
2
Order By: Relevance
“…Many of these genetic markers have been developed along the years, and from an early phase many of them have been applied to the genus Prunus, starting with the construction of a genetic map for improving breeding selection in peach (Chaparro et al, 1994). At least three genetic linkage maps of apricot have been published already (Hurtado et al, 2002;Vilanova et al, 2003;Lambert et al, 2004). Apricot diversity and genetic relationships have been studied using isozymes (Byrne and Littleton, 1989;Badenes et al, 1996), restriction fragment length polymorphisms (RFLPs) (De Vicente et al, 1998), random amplified polymorphic DNA (RAPDs) (Badenes et al, 2000), amplified fragment length polymorphisms (AFLPs) (Hagen et al, 2002;Hurtado et al, 2002) and sequence characterised amplified regions (SCARs) (Mariniello et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these genetic markers have been developed along the years, and from an early phase many of them have been applied to the genus Prunus, starting with the construction of a genetic map for improving breeding selection in peach (Chaparro et al, 1994). At least three genetic linkage maps of apricot have been published already (Hurtado et al, 2002;Vilanova et al, 2003;Lambert et al, 2004). Apricot diversity and genetic relationships have been studied using isozymes (Byrne and Littleton, 1989;Badenes et al, 1996), restriction fragment length polymorphisms (RFLPs) (De Vicente et al, 1998), random amplified polymorphic DNA (RAPDs) (Badenes et al, 2000), amplified fragment length polymorphisms (AFLPs) (Hagen et al, 2002;Hurtado et al, 2002) and sequence characterised amplified regions (SCARs) (Mariniello et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Minor QTL were discovered in the Polonais 9 SEO progeny in LG3 and LG5 of both SEO and Polonais [50]. The main QTL on LG1 was upheld by Sicard et al [51] establishing new microsatellite (SSR) markers flanking the QTL and by Lalli et al [52] in a backcross population of SEO 9 Vestar and was again confirmed by Soriano et al [46] in the extended F2 Lito selfed progeny.…”
Section: Kostina Et Al Compared the Inheritance Of Dormancy Length Imentioning
confidence: 90%
“…Using the information found on the T×E map, other maps were constructed and genetic analyses were performed that were associated with agronomic traits in almond populations (Joobeur et al, 2000;Ballester et al, 2001), almond × peach (Jáuregui et al, 2001;Bliss et al, 2002), apricot (Vilanova et al, 2003;, and peach (Dettori et al, 2001;Yamamoto et al, 2001;Etienne et al, 2002;Foulongne et al, 2003). However, the use of these maps is limited in Prunus because most were constructed with RFLPs that require complex and laborious laboratory procedures.…”
Section: Construction Of Genetic Mapsmentioning
confidence: 99%
“…The T×E map was thus expanded to 562 markers covering 519 cM with a mean density of 0.92 cM per marker; 87% of the loci corresponded to known DNA sequences and 37% of these were associated with a putative protein. Comparing the positions of the anchor markers of the T×E map (RFLPs, SSRs, and isoenzymes) with those of maps constructed with other Prunus populations (Viruel et al, 1995;Joobeur et al, 2000;Ballester et al, 2001;Jáuregui et al, 2001;Dettori et al, 2001;Yamamoto et al, 2001;Etienne et al, 2002;Bliss et al, 2002;Vilanova et al, 2003;Foulongne et al, 2003;Lambert et al, 2004), it was found that the genomes of the diploid (2n = 16) species peach, almond, apricot, cherry, P. davidiana (Carrière) N.E. Br., P. cerasifera, and P. ferganensis (Kostov & Rjabov) Kovalev & Kostov are essentially co-linear; it was therefore concluded that the genus Prunus can be treated as a single genetic unit.…”
Section: Construction Of Genetic Mapsmentioning
confidence: 99%